Kajian Variasi Massa Karbon Aktif dan Waktu Kontak terhadap Kinetika Adsorpsi Ion Logam Besi (Fe) pada Limbah Cair Batik Cual - Aprilianti, Rena; Aldila, Herman; Kurniawan, Widodo Budi (Jurnal Riset Fisika Indonesia, 2024)
Cual batik liquid waste discharged directly into the environment can cause environmental problems due to containing various heavy metals such as iron metal (Fe). Adsorption method is one of the efforts to reduce heavy metal content in wastewater. This study utilises activated carbon from coconut shell waste to be used as a heavy metal adsorbent. The activated carbon used is the result of physical and chemical activation processes. Based on SEM results, activated carbon has pores with a pore diameter of 81.84 µm and a surface area of 0.2315 cc/g. The adsorption process was carried out using activated activated carbon with mass variations of 0.25 grams, 1.5 grams, and 1.75 grams. Meanwhile, the contact time variations used were 0, 40, 80, 120, and 160 minutes. The results showed that the most optimum mass variation of activated carbon to absorb Fe metal was 1.5 grams with a contact time of 80 minutes which left a residual Fe metal of 0.161 ppm.